RESEARCH OF PHENOLIC COMPLEX OF LEAVES OF MESPILUS GERMANICA L. - N. N. Vdovenko-Martynova (Фармация и фармакология (Пятигорск), 2015)
Leaves of Mespilus germanica L. from Rosaceae family gathered in Kabardino Balkaria regions and in Botanical garden of Pyatigorsk Medical and Pharmaceutical Institute. The purpose of the study is examination of phenolic compounds in the raw materieals under analysis. Qualitative composition and quantitative identification of phenolic compounds in the air-dry raw materials of samples under study was done using qualitative reactions and high performance liquid chromatography method (HPLC). 13 compounds were received, 8 of them were identified as the substances of phenolic origin: flavonoids (quercetine, taxofolin, luteolin), hydroxycoric acids (gallic, chlorogenic, ferulic), polyphenolic compounds (epigallocatechin gallate, epicatechin). The sum of identified phenolic compounds amounted to 78,24% of all compounds found by the given method.